Management Development and the Supply Chain Manager of the Future. - Mangan, John; Christopher, Martin (MCB UP Ltd/Emerald Group Publishing Limited, 2005)
With the growing acceptance of logistics and supply chain management as critical business concerns, there is an emerging realisation that more investment is needed to develop appropriate managerial skills and competencies. This paper explores the challenges for management development that arise as organisations seek to bridge the gap between current capabilities and those required for future success. The results of an exploratory research programme are summarised and, drawing on these findings, a tentative skills profile for the logistics and supply chain manager of the future is advanced.
Keywords: Competences; Learning; Logistics; Management development; Skills; Supply chain management